Gugatan Perwakilan Kelompok (Class Action) dalam Penegakan Hukum Lingkungan di Kalimantan Timur - Siti Kotijah (Fakultas Hukum Universitas Mulawarman, 2006)
Potency of Natural Resources which abundance have generated much environmental problems or conflict. There are many solutions to solve environmental conflict, one of the solution is called Class Action. Class Action procedures according to Peraturan Mahkamah Agung Republik Indonesia Nomor 1 Tahun 2002 tentang Acara Gugatan Perwakilan Kelompok. Existence of Class Action in East Kalimantan still untapped as one of the environmental law enforcement, Class Action still only limited to discourse, failure of Class Action is caused by lower understanding of East Kalimantan society about Class Action. Key words: gugatan perwakilan kelompok (Class Action), penegakan hukum lingkungan (environmental law enforcement)